Diagnostic categorization of erectile dysfunction using duplex color doppler ultrasonography and significance of phentolamine redosing in abolishing false diagnosis of venous leak impotence: A single center experience - Ravikanth, Reddy (Indian Journal of Radiology and Imaging, 2020)
Background and Aims: Erectile dysfunction (ED) is an inability to achieve and maintain erectile rigidity sufficient for satisfactory sexual performance. It is either organic or psychogenic in origin. This study was aimed at establishing vasculogenic causes among patients being evaluated for ED using Penile Doppler Ultrasound. Methods: Fifty-two consecutive patients with the clinical diagnosis of ED were evaluated with color Doppler ultrasound scan using a 7.5 MHz high-frequency linear transducer between July 2016 and June 2019. The examination was commenced 3 min after an intracavernosal injection with 10-20 μg of PGE1 and continued for 30 min. The measurements were obtained alternately from both deep penile arteries. The variables analyzed were the peak systolic velocity (PSV), end-diastolic velocity (EDV) and resistive index (RI), calculated as (PSV-EDV)/PSV. Erection Hardness was evaluated subjectively using the EH Score (EHS), a 5-point response score denoting how the patient would rate his erection. ED was subjectively assessed using the International Index of Erectile Function (IIEF-5) questionnaire. In patients with a diagnosis of vasculogenic ED, intracavernosal PGE1 injection was started with a 5 μg dose and then increased in 5 μg increments until the final dose of 20 μg was reached. Results: PSV of cavernosal arteries (CA) varied between 19.2 and 106.2 cm/s (mean: 43.8 ± 18.2) among the entire patients and between 19.7 and 80.2 cm/s (mean: 42.6 ± 11.3) among patients with arteriogenic ED. Arteriogenic ED was found in 8 patients (15.3%), while venogenic ED was observed in 12 patients, which constituted 23% of the entire study population and mixed arteriogenic-venogenic ED was found in 6 patients (11.5%) of the study population. DICC performed on patients diagnosed with venogenic ED on color Doppler ultrasonography revealed venous leakage and no statistically significant differences between results of DICC and color Doppler ultrasonography were found in EDV, RI, and PI measurements (P< 0.005). Among patients with venogenic ED and mixed arteriogenic-venogenic ED,2 patients had a normal erectile response and the remaining 16 received 2 mg phentolamine. A significant increase in PSV between baseline and 20 mg PGE1 (P < 0.001) was observed in all cases. Following phentolamine, there was a significant increase in grade of erection (P = 0.0001) and a significant reduction in the EDV (P = 0.0001). A reduction of the EDV to below 0.0 cm/s was observed in 12 patients. In patients with arteriogenic erectile dysfunction, mean (±standard deviation) duration of erection for consecutive doses of PGE1 5 μg, 10 μg, 15 μg, and 20 μg were 42.2±18.4, 55.4±24.1, 66.1 ± 31.1, and 83.3±36.7 minutes, respectively, with significant increase for each dose. In patients with veno-occlusive dysfunction, mean durations of erection significantly increased from 9.1±8.0 minutes at 10 μg to 19.2±9.8 minutes at 20 μg. Conclusion: In the current study, 50% of patients had vasculogenic ED and “false-positive’’ diagnosis of venous leakage was unmasked by phentolamine re-dosing. It is therefore imperative that patients with ED benefit from duplex color Doppler ultrasonography which is safe, cheap and non-ionizing diagnostic modality before initiating therapy as ED treatment is cause specific.
Keywords: Duplex color doppler ultrasonography; end diastolic velocity; erectile dysfunction; erection hardness score; International index of erectile function questionnaire; peak systolic velocity; phentolamine; prostaglandin – E1; time to erection